Analisis Perlakuan Akuntansi Pembiayaan Ijarah Bermasalah pada PT. Bank Syariah “X” di Indonesia - Muhammad Yusuf (Bina Nusantara University, 2013)
Disbursement of funds by Islamic banks expected to get results have direct implications to the fund owner. If the investments made by the Islamic banks have payments that are not smooth and even jammed, can result in a small earned income and income received by the owner of the funds raised to be too small. All types of financing provided by banks to customers have experienced financing problems. Based on the information and data obtained, the most problematic financing for 2010 is the ijara financing, which underlies the preparation of this study. Research uses descriptive method of analysis. The research objective was to determine how the application of PT. Bank Syariah “X” in ijara financing problems, how it compares ijara financing problems in PT Bank Syariah “X” with non-performing loans at conventional banks, and how it compares to compliancewith SFAS 107 on accounting ijara at PT. Bank Syariah “X”. The benefits of research for the PT Bank Syariah “X” can be an evaluation of the practice that has been done in Indonesia Islamic banking world. Bank Syariah “X”. Accounting records ijara financing for the financing of the reverse problem of scheduling has been agreed will be recorded as revenue ijara receivables. The conclusion of the study is the recording of the restructuredijara financing, PT Bank Syariah “X” will record the repayment of the existing contract and replace with a new contract that has been adjusted in both the number and schedule of installment payments previously agreed by the customer and the PT. Bank Syariah “X”. Ijarah accounting records adopted by the PT Bank Syariah “X” are in accordance with SFAS 107 on accounting ijara.